PENGARUH CAPITAL ADEQUACY RATIO (CAR), NON PERFORMING LOAN (NPL), BEBAN OPERASI PENDAPATAN OPERASI (BOPO) DAN LOAN TO DEPOSIT RATIO (LDR) TERHADAP NET INTEREST MARGIN (NIM) (Studi pada Bank Umum Swasta Nasional Devisa dengan Manajemen Konvensional yang T - Savanero Briliantoro; Saryadi . (Jurnal Ilmu Administrasi Bisnis, 2022)
Abstract: Banking is an institution that brings together those who need funds and those who have funds. One of the bank's assessments is the level of efficiency with financial ratios that can be seen in the financial statements. The level of efficiency is described by the NIM ratio. Based on data obtained from 18 Conventional Foreign Exchange National Private Commercial Banks, only 4 banks have NIMs in the healthy category (>6%), while other banks have NIMs in the unhealthy category (<6%). To maintain NIM in a healthy condition, it is necessary to know what factors influence it. This study aims to determine the effect of Capital Adequacy Ratio, Non Performing Loan, Operating Income Operating Expenses, and Loan to Deposit Ratio on Net Interest Margin (NIM). The population of this research is all National Private Foreign Exchange Commercial Banks with conventional management listed on the Indonesia Stock Exchange in 2015-2019. The data was taken through the official website of the Indonesia Stock Exchange and the Financial Services Authority and analyzed using the Classic Assumption Test, Correlation Coefficient Test, Coefficient of Determination Test, Simple Linear Regression Test, Multiple Linear Test, T Test, and F Test with the SPSS data processing application. The results showed that CAR had a significant positive effect on NIM, NPL had no effect on NIM, BOPO had a significant negative effect on NIM. BOPO is the ratio that most dominantly affects NIM, second is the CAR ratio, and the last is NPL, while LDR has no influence on NIM. From the results of this study, it is concluded that the better the CAR, NPL, BOPO, and LDR will increase the NIM at Conventional Foreign Exchange National Private Banks listed on the Indonesia Stock Exchange in 2015-2019 and BOPO is the most dominant ratio affecting NIM. The advice for banks is to always keep the bank's financial ratios in a healthy condition so that they can increase their net interest profits. Banks are also expected to be able to maintain the BOPO ratio in a healthy condition because BOPO has the most dominant influence on NIMKeywords: Capital Adequacy Ratio, Non-Performing Loan, Operating Expenses Operating Income, Loan to Deposit Ratio, Net Interest Margin